Designing Engineering System Multi Use Peristaltic Pump by 3D Printer - Hamza, Tabarek Ammar Sami; Saywan, Saif Muhammad Kazem; Sahi, Yaqin Haider Hsnawi; Jaber, Baneen Taher Faisal (American Journal of Botany and Bioengineering, 2025)
Peristaltic pumps are widely used in biomedical and industrial applications due to their precision, leak-free operation, and ability to handle sensitive fluids. However, optimizing their design for enhanced efficiency and durability remains a challenge. This study presents a 3D-printed peristaltic pump designed using a model-assisted approach to analyze pump performance before fabrication. The methodology involves numerical modeling, material selection for 3D printing, and experimental validation through pressure pulsation and volume displacement tests. Findings indicate that the proposed design improves flow rate consistency and reduces mechanical wear, making it suitable for biomedical applications and automated fluid control systems. These results highlight the potential of 3D printing in advancing peristaltic pump technology, offering cost-effective and customizable solutions for diverse applications.